Political ties between the Оttoman state and Byzantine empire (according to byzantine sources) (Journal of history, 2022)
In the XIV century, the Turkish conquest of Asia Minor and the establishment of the Ottoman sultanate made this state border with Byzantium.The interstate border shaped the conditions of the war and led to the emergence of political problems. At the same time, mutual good neighborly relations and political processes have been established between the states, which lasted more than a century and a half. Relations between the two states were at different levels, which depended on political issues. Byzantine sources provide new information about the relationship between these states. This scientific paper discusses the history of the Turko-Byzantine relationship, from the formation of the Ottoman Sultanate to the capture of Constantinople by the Turks according to Byzantine sources. Based on the information presented in the chronicles of medieval Byzantine authors, the movement of the Turks in Asia Minor in the XIV-XV centuries, their political pressure on Byzantium, as well as interstate diplomatic and trade relations are explored. The main directions of relations between the Ottoman Sultanate and Byzantium and their political significance are analyzed. The policy and expansion of the Ottomans in the Balkans and the position of the Byzantine Empire regarding the development of the Turkish state are studied. Under studying political events between the two states, conducting a comparative analysis and studying Byzantine sources are  considered one of the main tasks of the article.Key words: Ottoman state, Byzantine Empire, Byzantine sources, Byzantine chronicles, External relations.